RAIN-FED RICE FIELD MANAGEMENT TO IMPROVE FOOD PRODUCTIVITY: A CASE STUDY OF REMBANG REGENCY - Aang H Sularso; A Rina Herawati; Retno Sunu A (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
As the owner of the highest percentage of rain-fed rice fields in Central Java, Rembang Regency faces serious challenges in increasing food productivity due to dependence on rainfall, land degradation, and the impact of climate change. This study aims to analyze the governance of rain-fed rice fields to increase food productivity in Rembang Regency, as well as the factors that inhibit it. The research method uses a qualitative-descriptive approach through in-depth interviews with farmers and related stakeholders. Secondary data comes from regulations, data from the Central Statistics Agency (BPS), journals, books, and websites. The results show that rice productivity in Rembang averages 5.5-5.6 tons/ha, lower than the provincial average (5.69 tons/ha), with the main factor being limited water infrastructure (only 17.24% of land has access to reservoirs/irrigation). Farmers receive insufficient support and outreach to understand rainfed rice management. A lack of innovation and limited information on superior rice varieties prevent farmers from comprehensively understanding which rice seeds are more suitable for their needs based on climate conditions. Regulations are not supported by technical measures at the regional level and tend to operate without integrative coordination between stakeholders. Good rainfed rice management to achieve sustainable food security as targeted by the SDGs requires not only technical development but also improvements in agricultural governance, including coordination, participation, capacity, and policies. Infrastructure development must emphasize community participation and be village-based. With farmer collaboration and policy integration between relevant agencies, food security in Rembang is not impossible to achieve. This research is not only relevant to Rembang Regency, but also other regions with similar rainfed land characteristics in Indonesia and globally.